The Prediction of depression based on critical thinking and self-perception in men and women in Mashhad - Saburi, Sogol; Talebiyan sharif, Jafar; AbdeKhodaei, Mohammad Saeid (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to predict depression based on critical thinking and self-perception in men and women in Mashhad. Method: The research was descriptive-correlational. For this purpose, among the men and women of Mashhad who lived in the city in 1400-1399 were randomly selected and available as a research sample and were divided into two groups based on gender. Then, to measure the rate of depression among men and women in Mashhad, factors related to depression (gender, marital status, employment status, level of education) were identified and also the relationship between critical thinking and self-perception of depression among 200 people. The men and women of this city were studied. To achieve this goal, demographic information sheet, Depression Inventory (Beck, 1961), Critical Thinking Questionnaire (Watson-Glaser, 1980) and Self-Perception Questionnaire (Pourhossein, 2007) were used as research tools for both groups. Finally, the obtained data were analyzed by statistical methods of correlation and regression by SPSS software. Results: Findings from data analysis showed that there is a strong correlation between these two variables of depression and self-perception, between critical thinking and depression. The results of regression analysis showed that self-perception explains 24% of the variance and self-perception and critical thinking explain 28% of the variance and the research hypothesis is significant. Conclusion: The analysis of the findings also showed that there is a significant relationship between self-perception and critical thinking with depression. In general, according to the results of the research findings, it can be said that between the two variables of this study, critical thinking and self-perception together have a greater share of each in predicting depression.